Dental fissure sealing as a method of primary prevention of fissure caries - Скульська, Світлана Василівна (Actual Dentistry, 2019)
Aim: to explore the efficiency of use the hermetics to prevent childrens dental caries of permanent teeth. Materials and methods of research. The condition of healthy chewing surface of permanent molar teeth and premolar teeth among the children of 6–12 ages Hermetics «Dentalex-20, 21 F» and Siroup of 28 pupils of the 6 age of 6 and group of 30 pupils of the age of 12. Planned sanitation of the oral cavity. Accuracy in teeth cleaning. Results. The results if exploring have detected the decrease in fissure caries among. The children at the age of 6–12 when we use «Dentalex 20, 21F» and «Dentalex 12, 12F». Stomatolog Health has improved. Conditions. Contamination of the high efficiency in using hermetics for prevention of the dental caries of permanent teeth. Key words: prevention of dental caries, dental fissure Sealing, immature adamantine substance the intensity of caries